Organization of the Pharmaceutical Business, Drug Technology and Forensic Pharmacy: Modern Trends in The Development of the Science of Pharmaceutical Law During the Covid-19 Pandemic - Krasnianska, Tetiana; Ponomarenko, Mykola (SSP Modern Pharmacy and Medicine, 2022)
The COVID-19 pandemic has affected modern trends in the training of doctors and pharmacists and their professional development. At the same time, the pandemic contributed to the development of the science of pharmaceutical law, as a basis for optimizing the legislation of Ukraine regarding the organization of pharmaceutical affairs in pharmacies and health care institutions, and thanks to modern research on the search for drug technology, it contributed to the creation of vital vaccines for the prevention of the SARS-CoV-2 coronavirus. At the same time, during the COVID-19 pandemic, the health care and pharmaceutical industry, based on the principles of medical and pharmaceutical law, showed that specialists can minimize forensic pharmaceutical risks in the system of legal relations "doctor-patient-pharmacist-lawyer" by ensuring the access of patients, the population and health care institutions to the circulation of medicinal products of all clinical and pharmacological groups, nomenclature and legal groups and classification and legal groups, in accordance with ICD-11.